Pregnancy and birth after intracytoplasmic sperm injection with normal testicular spermatozoa in a patient with azoospermia and tail stump epididymal sperm - Povlsen,Betina B. (2015)
Main findings: An intriguing yet perplexing case report of a successful pregnancy and live birth with intracytoplasmic sperm injection using normal testicular sperm, after the finding of azoospermia in the semen analysis and discovering only tail stump abnormal sperm in the epididymis. Case hypothesis: A tail stump sperm defect of genetic origin was suspected. However, after obtaining normal testicular sperm we concluded that obstructive azoospermia, either idiopathic or secondary to multiple minor genital trauma was the plausible scenario. This has rendered the search of previous reports on a similar condition, but none was found. However, it has raised scientific thoughts for future research. Promising future implications: The importance of reporting this case is to alert urologists performing sperm retrieval that healthy and morphologically normal sperm may be found in the testis of azoospermic men with 100% tail stump epididymal sperm. Retrieval of normal testicular sperm obviates the need of a more complex investigation, including sperm electron microscopy. It also offers the possibility of utilizing such gametes for sperm injections rather than abnormal tail stump sperm that may be associated with a poor reproductive outcome.